The Impact of Motivation on Revisit Intention - Ahmad, Fahry; Fikriyah, Maya Rahmah (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2022)
The purpose of this study is to ascertain the motivational description and its impact on the intention to return to Mount Papandayan Nature Tourism Park during the Covid-19 pandemic. In order to acquire findings in the form of an overview of the motive for revisit intention at Mount Papandayan Nature Tourism Park during the Covid-19 pandemic, descriptive-verification research, a method known as an explanatory survey, was used in this study. 350 responses made up the 350 samples, who were tourists who went rock climbing on Mount Papandayan Nature Tourism Park during the Covid-19 epidemic. In this study, a non-probability sampling methodology called incidental sampling was utilized to determine the sample size. Research instruments in the form of questionnaires that were sent to respondents and observations were employed in data gathering approaches. Validity and reliability tests, the classical assumption test, the multiple linear regression test, the f test (simultaneous), and the t test were all employed to analyze this (partial). Test results revealed that during the Covid-19 epidemic, motivation had an impact on visitors' intentions to return to Mount Papandayan Nature Tourism Park. The number of visitors to Mount Papandayan Nature Tourism Park who are highly motivated is evidence of this. as well as the desire to return and to refer friends, family, and acquaintances.Keywords: Sport Tourism, Motivation, and Revisit Intention.